1986
DOI: 10.1177/135050768601700315
|View full text |Cite
|
Sign up to set email alerts
|

Developing Conflict Management Skills in Hong Kong: An Analysis of some Cross-Cultural Implications

Abstract: This paper reports the results of an empirical study into the orientations towards conflict and preferred conflict management styles of Chinese managers in Hong Kong. The differences in styles between Chinese and Western managers are then traced back to aspects of Chinese culture and traditional values. The difficulties caused by these contrasting styles, both for the transfer of western managerial practices and for the operation of multi-ethnic organisations in Hong Kong, are noted. Similarly, the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 11 publications
3
41
1
Order By: Relevance
“…They argued with team members when they strongly disagreed with them. These behaviours contradict the traditional patterns of communication of collectivist Chinese as reported in previous studies (Brew and Cairns, 2004;Gao, 1998;Tang and Kirkbride, 1986;Yum, 1988). It is also interesting to find that some Western expatriate managers place a high emphasis on good relationships.…”
Section: Leadership Stylescontrasting
confidence: 58%
See 1 more Smart Citation
“…They argued with team members when they strongly disagreed with them. These behaviours contradict the traditional patterns of communication of collectivist Chinese as reported in previous studies (Brew and Cairns, 2004;Gao, 1998;Tang and Kirkbride, 1986;Yum, 1988). It is also interesting to find that some Western expatriate managers place a high emphasis on good relationships.…”
Section: Leadership Stylescontrasting
confidence: 58%
“…Traditional cultural dichotomies (Brew and Cairns, 2004;Gao, 1998;Tang and Kirkbride, 1986;Yum, 1988) predicted that the collectivist Chinese are rather indirect, and rely on 96…”
Section: Literature Review Collectivism Vs Individualismmentioning
confidence: 99%
“…Chinese people have been found to use approaches that short-circuit or diffuse open conflict and avoid face-to-face confrontation (Bond, Wang, Leung, & Giacalone, 1985;Chiao, 1981). Tang and Kirkbridge ( 1986) found that Hong Kong Chinese favored compromise approaches over conflict, whereas their British counterparts favored direct giveand-take collaboration.…”
mentioning
confidence: 97%
“…This was attributed to their assertive styles (Tang and Kirkbride, 1986). Individuals that traditionally maintain a lower status, such as females, contribute less in group situations than do high-status individuals (Kimble and Musgrove, 1988).…”
Section: Communicationmentioning
confidence: 98%